(3CfhGQ GdabGgIs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
(3cJGH GdUdGI hhLhHgG aj GdLedI ef VQhQjGJ GdOjf aeSJMdgG cGaQ(B...s
(3BNQgG (B:s
(3hdeG cGfJ fjI GdbVGFjI hGdCOGFjI ZjQ ebheI ddaYd ZjQ GdeWdhH Sgd GdCeQ aj GdHMK Yf chfgG bVGA HYO NQhL GdhbJ Ch COGA Je cJGH GdRcGI(B...s
(3aj JQJjH ChQGbgG GVWQGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B534s
(3GdPQjYI(B:(3L(B2(3,U(B244(3,Qbe (B1702s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis